2005
DOI: 10.2106/jbjs.d.01915
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of a Durasul Highly Cross-Linked Polyethylene Acetabular Liner for Total Hip Arthroplasty at Five Years

Abstract: While the qualitative wear pattern of the highly cross-linked polyethylene liner was the same as that of the conventional polyethylene liner, the annual linear wear rate was 45% of that seen with the conventional polyethylene liner. Therefore, we believe that these early data support the continued use of this highly cross-linked polyethylene liner for total hip arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(46 citation statements)
references
References 18 publications
4
40
1
1
Order By: Relevance
“…This supports the in vitro testing of similar types of polyethylene [24].The lower wear rates we found are consistent with those in other studies showing a reduction in wear at 5 years. Engh et al [11] and Bitsch et al [1] showed reduced wear with polyethylene from the same manufacturer as the HXLP in our study and other authors have reported similar findings with HXLP from other manufacturers including Crossfire by Stryker (Kalamazoo, Michigan) [6], and Durasul from Zimmer (Warsaw, Indiana) [10]. The study of Engh et al [11] differed from ours because it used lateralized liners and two different types of femoral stem.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This supports the in vitro testing of similar types of polyethylene [24].The lower wear rates we found are consistent with those in other studies showing a reduction in wear at 5 years. Engh et al [11] and Bitsch et al [1] showed reduced wear with polyethylene from the same manufacturer as the HXLP in our study and other authors have reported similar findings with HXLP from other manufacturers including Crossfire by Stryker (Kalamazoo, Michigan) [6], and Durasul from Zimmer (Warsaw, Indiana) [10]. The study of Engh et al [11] differed from ours because it used lateralized liners and two different types of femoral stem.…”
Section: Discussionsupporting
confidence: 74%
“…HXLP was developed to reduce wear and osteolysis. One in vitro study [24] suggests it is more resistant to wear, but limited longer term clinical evidence is available to document whether it does [1,6,10,11]. To confirm these studies we asked whether using HXLP would reduce the wear of polyethylene in primary total hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed liners that displayed negative wear, but nonetheless our average wear rates were positive for both crosslinked groups, indicating wear was occurring. Similarly, clinical studies of wear in acetabular components reported positive, albeit low, wear rates [4,5,7,10,23], suggesting patients are engaging in activities beyond those simulated with conventional hip wear testing conditions. Based on the higher stresses that occur with thinner liners [21], we expected wear and damage would be greater with the thinner liner.…”
Section: Discussionmentioning
confidence: 97%
“…When used in conventional head sizes, crosslinked polyethylene has led to marked reductions of 40% to 95% in wear as measured clinically from serial radiographs and radiostereometric measurements [4,5,7,10,23]. Laboratory experiments using a hip simulator demonstrated reduced wear could be expected with larger heads (up to 46 mm in diameter) and 3-mm thick highly crosslinked polyethylene liners when tested under normal gait conditions and orientation [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, wear particles are the leading cause of osteolysis and reportedly subsequent implant loosening [3,4,12,15,32,48] and a major cause of failure of THA [21]. Boutin introduced ceramic-onceramic (COC) bearings as an alternative to the metal-onpolyethylene bearings most commonly used in 1971 [7].…”
Section: Introductionmentioning
confidence: 99%